Modelo de estrategia de cuentos incompletos para las habilidades básicas de pensamiento crítico y creativo en niños de educación inicial - Vasquez, Sonia (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a thesis presented at the César Vallejo University, whose objective was to design an incomplete story strategy model to develop critical and creative thinking in initial education students from Chiclayo, for this a quantitative approach was used and the research was basic at a propositional level with a non-experimental design, we worked with a sample of 92 children from the I.E.I No. 004 of Chiclayo who were randomly selected and after designing the instrument for collecting information, which was a test, it was taken as results that more than half of the 4-year-old children presented a medium level of critical and creative thinking, a situation that is sought to be resolved through the design and proposal of an incomplete story strategy model that will contribute to solving the detected problem, the same that was validated at the discretion of expert judgment who gave their agreement both in the design and in its applicability , thus concluding that said design is a novel contribution to education by allowing students to improve these thoughts when said proposal is applied.